Processi storici e forme della rappresentazione identitaria del territorio - Poli, Daniela (Scienze del Territorio, 2017)
The coevolutionary dimension of territories, understood as a match and a con-stant re-elaboration among socio-economic dynamics, environmental features and territorial structure, is a central assumption of the territorialist thinking. Ter-ritory is in fact both the material and cognitive outcome of a long historical pro-cess, marked by continuity and fractures, which has deposited sediments to be incessantly re-possessed and re-elaborated by the settled societies. The meth-odological appeal to a historical perspective appears inevitable. In the current phase of de-territorialisation, historical configurations take on both a cognitive and a design value. In an interested perspective, the history of territories is put into interaction with the needs of the present, to understand the reasons and dynamics of the longue-durée and to identify the invariant rules of construction, maintenance and reproduction of territorial heritage. The heritage representa-tion depicts such processes, giving great importance to the relational and com-municative dimension of figuration. This paper deals with the use of operational and cartographic tools for the morphologic and the historical-structural inter-pretation of territory, consistent with the methodology illustrated in the paper by Alberto Magnaghi in this same number. It consists of two parts: 1) the mor-pho-typological representation; 2) the historical-structural analysis for the defi-nition of territorialisation processes and heritage syntheses.